2000
DOI: 10.1111/j.1741-4520.2000.tb00881.x
|View full text |Cite
|
Sign up to set email alerts
|

Teratogenic effect of bis‐diamine on embryonic rat heart

Abstract: Bis‐diamine induces conotruncal anomalies including persistent truncus arteriosus, tetralogy of Fallot, interruption of the aortic arch, and ventricular septal defect in rat embryos when administered to the mother. Bis‐diamine also induces extracardiac malformations including thymic hypoplasia, facial dysmorphism, forelimb anomalies and diaphragmatic hernia. However, the teratogenic mechanisms of this chemical in early developing rat hearts have not been fully established. Chimeric studies in chick and quail e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Previous studies showed that cardiovascular anomalies were frequently induced when bis‐diamine was administered to pregnant female rats on ED 10.5, and this animal model has been used to understand the pathogenesis of conotruncal anomalies (Taleporos et al, 1978; Hayakawa et al, 1983; Okamoto et al, 1984; Momma et al, 1990, 1991; Tasaka et al, 1991, 1993; Kuribayashi and Roberts, 1993; Momma and Ando, 1994, 1995; Jackson et al, 1995). Until now, it has been shown that bis‐diamine establishes cardiovascular defects by disturbing the migration of neural crest cells and myocardial differentiation, proliferation, and apoptosis thorough placental transfer (Ikeda et al, 1984; Binder, 1985; Choy et al, 1999; Fujino et al, 1999; Nakagawa et al, 2000; Nishijima et al, 2000; Okamoto et al, 2004). The present study showed that this animal model is useful for understanding the mechanisms of arrhythmias associated with human congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that cardiovascular anomalies were frequently induced when bis‐diamine was administered to pregnant female rats on ED 10.5, and this animal model has been used to understand the pathogenesis of conotruncal anomalies (Taleporos et al, 1978; Hayakawa et al, 1983; Okamoto et al, 1984; Momma et al, 1990, 1991; Tasaka et al, 1991, 1993; Kuribayashi and Roberts, 1993; Momma and Ando, 1994, 1995; Jackson et al, 1995). Until now, it has been shown that bis‐diamine establishes cardiovascular defects by disturbing the migration of neural crest cells and myocardial differentiation, proliferation, and apoptosis thorough placental transfer (Ikeda et al, 1984; Binder, 1985; Choy et al, 1999; Fujino et al, 1999; Nakagawa et al, 2000; Nishijima et al, 2000; Okamoto et al, 2004). The present study showed that this animal model is useful for understanding the mechanisms of arrhythmias associated with human congenital heart disease.…”
Section: Discussionmentioning
confidence: 99%
“…N,N′ bis (dichloroacetyl) diamine‐1,8‐octa‐methylene diamine (bis‐diamine) is known to induce characteristic conotruncal anomalies, including patent truncus arteriosus, tetralogy of Fallot, interruption of the aortic arch, and ventricular septal defect in embryos when administered to pregnant female rats (Taleporos et al, 1978; Hayakawa et al, 1983; Okamoto et al, 1984; Momma et al, 1990, 1991; Tasaka et al, 1991, 1993; Kuribayashi and Roberts, 1993; Momma and Ando, 1994, 1995; Jackson et al, 1995). Previous studies using this animal model have shown that bis‐diamine caused anomalous neural crest cell migration into the hearts and subsequent abnormal conotruncal division (Ikeda et al, 1984; Binder, 1985; Choy et al, 1999; Fujino et al, 1999; Nakagawa et al, 2000), pericardial defects (Nishijima et al, 2000), and poor myocardial proliferation and growth (Okamoto et al, 2004). In order to determine the mechanisms of arrhythmias associated with congenital heart defects, we examined the embryonic development of the cardiac conduction system in this animal model.…”
Section: Introductionmentioning
confidence: 89%
“…N,N′‐bis (dichloroacetyl) diamine‐1,8‐octa‐methylene diamine (bis‐diamine) is known to induce characteristic cardiovascular anomalies, including such conotruncal anomalies as patent truncus arteriosus, tetralogy of Fallot, interruption of the aortic arch, and ventricular septal defect in rat embryos when administered to the mother (Tareporos et al, 1978; Hayakawa et al, 1983; Okamoto et al, 1984; Momma et al, 1990, 1991; Tasaka et al, 1991, 1993; Kuribayashi and Roberts, 1993; Momma and Ando, 1994, 1995; Jackson et al, 1995). In previous reports, this chemical was proposed to disturb the normal migration of cardiac neural crest cells into the heart, leading to the induction of the conotruncal anomalies (Ikeda et al, 1984; Binder, 1985; Choy et al, 1999; Fujino et al, 1999; Nakagawa et al, 2000; Nishijima et al, 2000). Because the human conotruncal anomalies are also induced by abnormal neural crest cell migration into the heart, this animal model appears useful for studying myocardial cell growth and proliferation or ventricular development in the heart exhibiting a conotruncal anomaly.…”
Section: Introductionmentioning
confidence: 99%